How to write essays and dissertations : a guide for English literature students - Fabb, Nigel; Durant, Alan (Routledge, Taylor & Francis Group, 2014)
This essential guide to writing essays and dissertations for English literature students offers step-by-step instruction on each stage of writing, from organising initial ideas through to submitting a completed piece of work. It also explains the general principles that underlie essay topics and exam questions, building on a description of those principles to help students develop effective writing and editing strategies. Fabb and Durant offer a clear account of what makes a successful essay in literary studies, and demonstrate why alternative forms of argument and presentation are not considered to work so well. They outline various ways of solving problems encountered during the process of writing, and emphasise the importance of finding solutions that suit the writer and the topic.